Arbitraging the Basel securitization framework: Evidence from German ABS investment - Matthias Efing (Deutsche Bundesbank, 2015)
This paper provides evidence for regulatory arbitrage within the class of assetbacked securities (ABS) based on individual asset holding data of German banks. I find that those banks operating with tight regulatory constraints pick the securities with the highest yield and lowest collateral quality among ABS with the same regulatory risk weight. This ABS selection allows banks to increase the return on the capital required for an ABS investment by a factor of four.
Keywords: G01; G21; G24; G28; 330; regulatory arbitrage; asset-backed securities; risk-taking; credit ratings